Assessing Language Teachers’ Technological Pedagogical Content Knowledge (TPACK): EFL Students’ Perspectives - Jalil Fathi; Saman Yousefifard (Research in English Language Pedagogy, 2019)
Technological Pedagogical Content Knowledge (TPACK) is considered as a valuable frame for describing and understanding technology integration into different educational settings, including English as a Foreign Language (EFL) classroom. There is an accumulated body of literature on TPACK among teachers engaged in different areas of education. However, few studies have addressed the assessment of TPACK through students’ perspectives in EFL settings. To address this gap, the purpose of this study was set to assess Iranian EFL students’ perspectives regarding their teachers’ TPACK. A total of 148 Iranian EFL students participated in this survey study. The data were collected through administering a previously validated TPACK questionnaire to the participants of the study. The findings obtained from the survey indicated that most EFL students perceived that their EFL teachers excelled in four components of TPACK such as technological knowledge (TK), pedagogical knowledge (PK), content knowledge (CK), and pedagogical content knowledge (PCK), but the teachers were perceived to be relatively less proficient in the other three components of the scale such as technological content knowledge (TCK), technological pedagogical knowledge (TPK), and TPACK. The results suggest that Iranian EFL teachers may require further training in these latter elements of the TPACK to gain the required proficiency to integrate technology more effectively into their language classrooms.